2020
DOI: 10.1186/s40985-020-00126-5
|View full text |Cite|
|
Sign up to set email alerts
|

HPV knowledge and vaccine acceptance among European adolescents and their parents: a systematic literature review

Abstract: Background: Since the introduction of HPV vaccines, several studies have been conducted in different countries to assess HPV knowledge and vaccine acceptance. The aim of this study was to perform a systematic literature review to summarize results and identify factors associated with HPV knowledge and vaccine acceptance in adolescents and their parents and to compile the measurement tools used in the published research studies performed in European countries where HPV is licensed. Methods: A systematic literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
55
2
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(79 citation statements)
references
References 78 publications
3
55
2
6
Order By: Relevance
“…In the original publication of this article [ 1 ] a large part of Table 2 was missing due to an error during typesetting.…”
mentioning
confidence: 99%
“…In the original publication of this article [ 1 ] a large part of Table 2 was missing due to an error during typesetting.…”
mentioning
confidence: 99%
“…Çin'de bu oran %7,4'ü iken Amerika'da yapılan çalışmada katılımcıların çoğunluğu son üç yılda en az bir kez Pap smear testi yaptırmıştır. 35 Pap smear testi yaptırma, kadınlar için farklı anlamlar taşıyabilir. Cinsel organlar özellikle geleneksel ve tutucu toplumlarda mahrem olarak algılanmaktadır.…”
Section: Discussionunclassified
“…12 Özellikle düşük gelirli ve devlet sigortası olmayan bireylere hastalığın geç dönemlerinde kanser teşhisi konulması, standartların altında klinik bakım/hizmet alınması ve kansere bağlı kayıpların yaşanması olasıdır. 35 Serviks kanserinin yüksek insidans ve mortalite oranları ile Pap smear taramasına yetersiz katılım, düşük sosyoekonomik düzeyle ilişkilidir. 19 Human Papilloma Virüs aşılama programları 2018 yılından itibaren 80 ülkede/bölgede uygulanmaya başlanmıştır.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…According to the systematic review published by Lopez et al, higher acceptance of human papillomavirus (HPV) vaccine was associated most consistently with female gender and younger age of respondent parent, female gender of the adolescent, higher household income and previous childhood vaccinations [35]. A recent study by Polla et al revealed that among parents, those who were unmarried were more likely to be hesitant about the importance of HPV vaccination [36].…”
Section: Discussionmentioning
confidence: 99%